2012
DOI: 10.1080/19942060.2012.11015415
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combustor Geometry on Performance of Airblast Atomizer Under Sub-Atmospheric Conditions

Abstract: ABSTRACT:One of the certification requirements that a jet engine has to fulfil is its altitude relight capability. Relighting an aero gas turbine engine at high altitudes is more challenging than at sea level conditions. The pressure, air velocity, and temperature within the combustor at such conditions are very low, hindering the fuel atomization and evaporation process. After ignition, combustion efficiency can be relatively low due to the poor fuel atomization quality, leading to slow shaft acceleration rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
0
10
0
2
Order By: Relevance
“…As can be seen, there is an increase of the overall combustion duration from 45 • for B0 to 46.7 • for B20 blend due to higher droplet diameters which lead to slower combustion. The higher the Sauter mean diameter, the less easy it is for a droplet to evaporate [18]. On the other hand, burn duration 0-10% and 0-50% are lower using B20, leading to faster combustion during combustion premixed phase until crank angle of 50% burn point.…”
Section: Combustion Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen, there is an increase of the overall combustion duration from 45 • for B0 to 46.7 • for B20 blend due to higher droplet diameters which lead to slower combustion. The higher the Sauter mean diameter, the less easy it is for a droplet to evaporate [18]. On the other hand, burn duration 0-10% and 0-50% are lower using B20, leading to faster combustion during combustion premixed phase until crank angle of 50% burn point.…”
Section: Combustion Characteristicsmentioning
confidence: 99%
“…The higher the Sauter mean diameter, the less easy it is for a droplet to evaporate [18]. On the other hand, burn duration 0-10% and 0-50% are lower using B20, leading to faster combustion during combustion premixed phase until crank angle of 50% burn point.…”
Section: Combustion Characteristicsmentioning
confidence: 99%
“…The suitable volumes of air in the liner of the primary, secondary and dilute holes were found to be 22.51%, 22.93% and 54.56%, respectively [11]. However, the volume of combustion chamber did not have an effect on creating CRZ because the air/fuel ratio was still constant [12]. In addition, the turbulence model in this work showed that the turbulence k-ɛ standard gave better results for combustor prediction than other turbulence models [11,13,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Lefebvre and his team obtained series of important achievements on twin-fluid atomizers and proved that twin-fluid atomizers have many advantages over other types of atomizers, since they require lower pump pressures and produce a finer spray [4]. The applications of twin-fluid atomizer are focused on engine combustion [6,7], humidification [8], gas cooling [9], spray painting [10] and spray drying [11], etc.…”
Section: Nomenclaturementioning
confidence: 99%